(untitled) - Jerrold Marsden (New York, 1984)
This book, the third of a three-volume work, is concerned with multivariable calculus, and begins with the necessary material from analytic geometry. It goes on to cover partial differentation, the gradient and its applications, multiple integration, and the theorems of Green, Gauss, and Stokes. Many problems are included, and extensive exercises are given at the end of each section
Keywords: calculus